Azobenzene-modified antisense oligonucleotides for site-specific cleavage of RNA with photocontrollable property. Issue 96 (29th September 2016) - Wang, Xingyu; Liang, Xingguo
Abstract : Photoresponsive azobenzene-modified antisense oligonucleotides for site-specific RNA cleavage by RNase H. Abstract : We presented a RNase H-based strategy for site-specific RNA cleavage using azobenzene-modified antisense oligonucleotides (ASO). The results showed that RNase H can bind to the ASO–RNA heteroduplex, and cut the RNA strand at predetermined sites. Moreover, cleavage rate can be regulated by photoirradiation, with a 5-fold photomodulation efficiency at most.